Henoch-Schonlein Purpura in Adult with Gastrointestinal and Renal Involvement - Devi, Aprilin Krista; Umborowati, Menul Ayu; Anggraeni, Sylvia; Damayanti, Damayanti; Cita Rosita Sigit Prakoeswa (Faculty of Medicine, Universitas Airlangga, 2023)
Background: The pathogenesis of Henoch-Schonlein Purpura (HSP), a multisystem organ-involved small vessel vasculitis, is unknown. HSP is more common in youngsters than in adults. HSP is associated with a history of malignancies, medications, vaccinations, and upper respiratory tract infections. Painful purpura, arthritis, stomach discomfort, and renal involvement are symptoms that may be seen in HSP patients. Adult patients had a much higher rate of renal involvement than children. Purpose: To report a case of HSP in an adult with gastrointestinal and renal involvement. Case: A 45-year-old man complained of an arm, leg, and waist rash for two weeks before admission to the hospital. He also has stomach pains, nausea, and vomiting to deal with. His symptoms have just appeared now for the first time. During a renal function test, blood urea nitrogen (BUN) and creatine serum levels rose. On a urinalysis, proteinuria and microscopic hematuria were found. Leucocytoclastic vasculitis was discovered during the histopathology investigation. HSP diagnosis was based on the ACR and ICC criteria. The patient was given 3x2 tablets of 0.5 mg dexamethasone, 3x2 tablets of cetirizine, 2x10 mg lisinopril, 2x50 mg ranitidine injection, and 2 grams ceftriaxone. Discussion: The clinical symptoms of HSP are used to make the diagnosis. In the vast majority of instances, the treatment is only supportive therapy. Corticosteroid usually are usually used for HSP with multisystem organ involvement to reduce pain severity and faster resolution of renal manifestation. Conclusion: Follow up on renal function is needed to monitor the worsening of renal disease.